Given:
The equation 3(x - 4) + 5 = 2x - 2(3 - x).
Required:
Give the reason for each step of the solution.
Explanation:
Step 1: Simplify both sides of the equation.
[tex]\begin{gathered} 3(x-4)+5=2x-2(3-x) \\ \text{ Dsitribute the equation} \\ 3x-12+5=2x-6+2x \\ \text{ Combine like terms} \\ 3x-7=4x-6 \end{gathered}[/tex]Step 2: Subtract 4x from both sides
[tex]\begin{gathered} 3x-7-4x=4x-6-4x \\ -x-7=-6 \end{gathered}[/tex]Step 3: Add 7 to both sides.
[tex]\begin{gathered} -x-7+7=-6+7 \\ -x=1 \end{gathered}[/tex]Step 4: Divide both sides by -1.
[tex]\begin{gathered} \frac{-x}{-1}=\frac{1}{-1} \\ x=-1 \end{gathered}[/tex]Answer:
Value of x = -1